Revealing the Charm of Exploring Tourism Destinations That Are Going Viral Lately - Alifianti, Anggun Sukma; Rahmadani, Celina; Priyantini, Dayu Winda; Damayanti, Sri; Pranata, Andi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to reveal the phenomenon of the charm of tourism destination exploration which has become viral in the recent period. By analyzing social media trends, traveler reviews and recent news developments, this research explores the factors that have led to the rapid popularity of certain tourism destinations. Through a qualitative approach, data is analyzed to understand how extensive exposure on social media and intense promotions influence tourist interest and visits. The results show that visual factors, cultural uniqueness, and influencer recommendations play a big role in building public interest in viral tourist destinations. The implications of these findings can help in tourism marketing strategies to increase the attractiveness and popularity of tourist destinations in the future.